2021
DOI: 10.32598/ijpcp.27.1.3246.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotion-focused Therapy on Anxiety, Depression and Difficulty in Emotion Regulation in Women With Binge Eating Disorder

Abstract: Objectives: This study aims to investigate the effect of Emotion-Focused Therapy (EFT) on depression, anxiety, and Difficulty in Emotion Regulation (DER) in women with Binge Eating Disorder (BED). Methods: This is a quasi-experimental study with pre-test/post-test/follow-up design using a control group. Study population consists of all women referred to the obesity clinics in Tehran in 2019. Of these, 40 were selected using a purposive sampling method and were randomly divided into two groups of intervention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…The study results also showed the significant effect of EFT on reappraisal at the posttest and follow-up stages. This finding is consistent with the results reported by Asmari Bardezard et al (37) who confirmed the effect of EFT on the difficulty of emotion regulation and acknowledged that EFT improves emotion self-regulation. In other words, the intrinsic and extrinsic processes known as emotions are in charge of regulating, assessing, and altering an individual's emotional responses when they get in the way of achieving their objectives.…”
Section: Discussionsupporting
confidence: 93%
“…The study results also showed the significant effect of EFT on reappraisal at the posttest and follow-up stages. This finding is consistent with the results reported by Asmari Bardezard et al (37) who confirmed the effect of EFT on the difficulty of emotion regulation and acknowledged that EFT improves emotion self-regulation. In other words, the intrinsic and extrinsic processes known as emotions are in charge of regulating, assessing, and altering an individual's emotional responses when they get in the way of achieving their objectives.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the results indicate a greater effectiveness of EFT compared to CBT in reducing experiential avoidance. Individuals with complicated grief typically engage in strategic attempts to escape or avoid stressful experiences, negative emotions, and suppress the expression of emotions (Asmaribardezard et al, 2018;Gesi et al, 2020;Greenberg et al, 2008;Sandberg & Knestel, 2011). The emotion-focused perspective believes that for treatment to occur, one must access the depths of painful experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Gharibpour, et al, 2019 ;Mennin, et al, 2015 ;Shaffer, et al, 2019 ;Sharifipour, et al, 2017 ;Sheikhi Gerakoui, et Gharibpour, et al, 2019 ;Mennin, et al, 2015 ;Shaffer, et al, 2019 ;Sharifipour, et al, 2017 ;Sheikhi Gerakoui, et al, Costa, et al, 2018;McCloskey, et al, 2008 ;Osma, et al, 2016 ) . Asmari, et al, 2021 ;Hewage, et al, 2018 ;McCloskey, et al, 2008 ;McCloskey, et al, 2022 ;Mennin, et al, 2015 ;Osma, et al…”
Section: The Effectiveness Of Emotion Regulation Therapy In Reducingmentioning
confidence: 99%